2014
DOI: 10.1371/journal.pone.0108464
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of Alpha-V Integrins Reduces Malignancy of Bladder Carcinoma

Abstract: Low survival rates of metastatic cancers emphasize the need for a drug that can prevent and/or treat metastatic cancer. αv integrins are involved in essential processes for tumor growth and metastasis and targeting of αv integrins has been shown to decrease angiogenesis, tumor growth and metastasis. In this study, the role of αv integrin and its potential as a drug target in bladder cancer was investigated. Treatment with an αv integrin antagonist as well as knockdown of αv integrin in the bladder carcinoma ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
18
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 55 publications
5
18
0
1
Order By: Relevance
“…39 Since then, αV together with β3, β5, β6, or β8 integrins has been widely studied in multiple cancers and numerous studies have shown the correlation of high αV integrin expression with cancer progression. [40][41][42][43][44] Conversely, inhibition of αV integrin is sufficient to block invasive activity in preclinical in vitro and in vivo models- 40,[45][46][47] and has been used as a therapeutic target for metastatic cancers in preclinical and clinical studies. 16,32,48 In this study, we show that αVβ3 heterodimer is found in HER2positive breast cells.…”
Section: Discussionmentioning
confidence: 99%
“…39 Since then, αV together with β3, β5, β6, or β8 integrins has been widely studied in multiple cancers and numerous studies have shown the correlation of high αV integrin expression with cancer progression. [40][41][42][43][44] Conversely, inhibition of αV integrin is sufficient to block invasive activity in preclinical in vitro and in vivo models- 40,[45][46][47] and has been used as a therapeutic target for metastatic cancers in preclinical and clinical studies. 16,32,48 In this study, we show that αVβ3 heterodimer is found in HER2positive breast cells.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the molecular mechanisms involved in the pro-tumourgenic function of HACE1, we demonstrated that HACE1 silencing induced a modification of the transcriptional programme in melanoma cells that was compatible with a decrease in cell movement and migration. Among the genes associated with these effects, ITGAV and ITGB1 were downregulated at the transcriptional level, and their involvement in cell migration has been extensively described [12,22]. Other genes, such as PLAU and SDC4, which promote cell invasiveness [23,24], were also downregulated by HACE1 silencing.…”
Section: Discussionmentioning
confidence: 99%
“…CDH2 is commonly up-regulated in various cancers, including colorectal cancer [14], prostate cancer [15], gastric cancer [16], bladder cancer [17] and lung cancer [18]. In addition, it is reported that CDH2 plays a significant part in epithelial-mesenchymal transition (EMT) [19].…”
Section: Introductionmentioning
confidence: 99%